(untitled) (Research, Society and Development, 2024)
Polycystic ovarian syndrome (POS) is a chronic endocrine disease characterized by the presence of small cysts in the ovaries. Hirsutism, insulin resistance, hair loss, menstrual disorders, infertility and acne are manifestations frequently associated with this disease. Given the complexity of the situation, the objective of this integrative review was to gather scientific findings that could support nutrition as a supporting strategy in the treatment of POS. To this end, 34 scientific articles published in Portuguese and English were collected in the National Library of Medicine (PubMed) and Google Scholar (Scholar) databases. Changes in lifestyle associated with diets that prioritize a diet with a low glycemic index, adequate from a qualitative point of view and associated with the practice of supplementation aimed at POS, reduce the patient’s symptomatology, impacting the reduction of comorbidities and improving the condition general patient.